2021
DOI: 10.1002/jso.26685
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the longitudinal effect of colorectal surgery on health‐related quality of life in patients with colorectal cancer

Abstract: Background and Objectives: Surgery for colorectal cancer (CRC) negatively affects health-related quality of life (HRQoL). Addressing shortcomings in literature, the purpose of this study was to evaluate the impact of surgery for CRC on the course of HRQoL from baseline up to 2 years after diagnosis.Methods: In this prospective, population-based study patients with newly diagnosed CRC were included between 2016 and 2019. HRQoL was assessed by the EORTC QLQ-C30 questionnaire over time both between and within sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 25 publications
(47 reference statements)
1
13
0
Order By: Relevance
“…Among functional scales of C30, only physical functioning (78.72) was found to be lower than TCI in our CRC patients and we found this similar to another study reported on all GI cancer in Pakistan (22). Physical functioning scores have been reported in a diverse range (62.9-90) in the published literature (14,16,18,27). This high variability is likely due to the variable stage of disease and the location of tumor as treatment modalities and stoma have signi cant effect on physical functioning of CRC patients.…”
Section: Resultssupporting
confidence: 87%
“…Among functional scales of C30, only physical functioning (78.72) was found to be lower than TCI in our CRC patients and we found this similar to another study reported on all GI cancer in Pakistan (22). Physical functioning scores have been reported in a diverse range (62.9-90) in the published literature (14,16,18,27). This high variability is likely due to the variable stage of disease and the location of tumor as treatment modalities and stoma have signi cant effect on physical functioning of CRC patients.…”
Section: Resultssupporting
confidence: 87%
“…However, in the Discussion, the authors did not analyze whether the stoma affects the HRQoL scores of rectal resection. 1 In our clinical work, we found that stoma can significantly reduce the quality of life of rectal resection, which is mainly due to the following reasons.…”
Section: Evaluating the Longitudinal Effect Of Colorectal Surgery On ...mentioning
confidence: 94%
“…We have read with interest the article published by Reudink et al 1 At present, more and more attention has been paid to the quality of life of patients after colorectal resection. 2 Although we believe it is a very interesting topic, we would like to offer the following points for your consideration.…”
Section: Evaluating the Longitudinal Effect Of Colorectal Surgery On ...mentioning
confidence: 99%
“…recovers in the majority of patients to baseline values within the first year after surgery [6][7][8]. Compared to the general population, HRQoL scores were only slightly attenuated in CRC patients 1 year after diagnosis [9].…”
mentioning
confidence: 92%
“…Studies evaluating HRQoL among CRC patients demonstrated that HRQoL substantially declines in the early postoperative period and recovers in the majority of patients to baseline values within the first year after surgery [6‐8]. Compared to the general population, HRQoL scores were only slightly attenuated in CRC patients 1 year after diagnosis [9].…”
Section: Introductionmentioning
confidence: 99%